Valorization of Spent Escherichia coli Media Using Green Microalgae Chlamydomonas reinhardtii and Feedstock Production - Zhang, Jian-Guo; Zhang, Fang; Thakur, Kiran; Hu, Fei; Wei, Zhao-Jun (Frontiers in Microbiology, 2017)
The coupling of Chlamydomonas reinhardtii biomass production for nutrients removal of Escherichia coli anaerobic broth is thought to be an economically feasible option for the cultivation of microalgae. The feasibility of growing microalgae in using Escherichia coli anaerobic broth (EAB) high in nutrients for the production of more biomass was examined. EAB comprised of nutrient-abundant effluents, which can be used to produce microalgae biomass and remove environment pollutant simultaneously. In this study, C. reinhardtii 21gr (cc1690) was cultivated in different diluted　E. coli anaerobic broth supplemented with trace elements under mixotrophic and heterotrophic conditions. The results showed that C. reinhardtii grown in 1×, 1/2×, 1/5× and 1/10×E. coli anaerobic broth under mixotrophic conditions exhibited specific growth rates of 2.71, 2.68, 1.45 and 1.13 day-1, and biomass production of 201.9, 184.2, 175.5 and 163.8 mg L-1, respectively. Under heterotrophic conditions, the specific growth rates were 1.80, 1.86, 1.75and 1.02day-1, and biomass production were 45.6, 29.4, 15.8 and 12.1 mg L-1, respectively. The removal efficiency of COD, total-nitrogen and total-phosphorus from 1× E. coli anaerobic broth was 21.51%, 22.41% and 15.53%. Moreover, the dry biomass had relatively high carbohydrate (44.3%) and lipid content (18.7%). Therefore, this study provides an environmentally sustainable as well economical method for biomass production in promising model microalgae and subsequently paves the way for industrial use.